Incidence of Gender in the Digital Competence of Higher Education Teachers in Research Work: Analysis with Descriptive and Comparative Methods - Francisco D. Guillén-Gámez; María J. Mayorga-Fernández; José A. Contreras-Rosado (MDPI AG, 2021)
The purpose of this study is to analyse and compare the level of digital competence of higher education teaching staff in research work through the use of ICT resources. For this purpose, an ex post facto design was employed together with an instrument composed of 30 items classified into seven dimensions: digital skills, digital ethics, digital flow, anxiety towards ICT, quality of ICT resources, intention to use ICT, and ICT integration. The sample consisted of a total of 1704 higher education teachers from all over Spain. The results showed that, overall, there were no significant differences in the level of digital competence of teaching staff between the two genders. However, significant differences were found in the following dimensions: digital skills, digital ethics, ICT anxiety, quality of ICT resources, and intention to use ICT. These findings highlight the urgent need for university institutions to propose training plans to improve the digital competences of their teaching and research staff in those dimensions that have been found to be deficient.